(untitled) (Revista de História Regional, 2007)
In memory and oral history of the contemporary Mbyá-Guarani there are recurrent references to the character named kechuíta. At first hand, the term refers a variant of the word Jesuit. In the ethnographical registers, its existence has been approached by some researchers such as CADOGAN (1971), VIETTA (1992) e GARLET (1997), receiving interpretation which sometimes conflict, and sometimes complement each other. In the historical registers, in turn, the reports about the contact, and the possible influence of the Inatian missionary show that these were few and seldom. From a relational exercise, we try to clear the possible connections of this mythological character and the historical figure of the Jesuit, trying to better understand the implications of interethnic contact in the culture and, in special, in the mythology of this ethnic group.